The motive of Hieros Gamos in Jesus’s Baptism in the Jordan River and in Jewish Kabballah - Jacobson, Ofir (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
This paper suggests an alternative interpretation of Christ’ baptism, and more precisely, of the dove's role in it. One of the main rituals in the Ancient East was the 'sacred marriage' (Hieros Gamos), the purpose of which was to assure abundance, prosperity, and cosmic fertility, and to validate the status of the king. In many cases, the actual crowning, which followed the main ritual, was performed by a dove, one of the symbols of the feminine partner in the sacred marriage – the great goddess.Through the centuries, this ancient ritual underwent extensive transformations and reforms, but even though the goddess seemed to have vanished, her disappearance was only an illusion. There is abundant evidence to show that the ritual reform did not suppress the old traditions and beliefs but merely hid them beneath the surface. This evidence suggests that the goddess reappeared, sometimes centuries later, manifesting herself in numerous guises, as, for example, in the Kabbalah and in Middle Eastern folk tradition. Furthermore, both textual and archeological findings indicate the continuous presence of the motive of the dove as a symbol of the goddess, who elects and coronates the king. The projection of this motive onto the familiar Christian scenario of Jesus’ baptism can shed new light on the survival of the ancient, forgotten, symbolic meaning of the dove as a female divine entity who chooses and crowns Christ.